1983
DOI: 10.1021/bi00292a029
|View full text |Cite
|
Sign up to set email alerts
|

Rapid kinetics of agonist binding and permeability response analyzed in parallel on acetylcholine receptor rich membranes from Torpedo marmorata

Abstract: Excitable acetylcholine receptor rich membrane fragments from Torpedo marmorata have been used to measure, in parallel, (1) the permeability response to the fluorescent cholinergic agonist Dns-C,-Cho (in the 0.1 pM to' millimolar concentration range) characterized by both the initial rate of Li+ transport and the rate of channel closure using the rapid-mixing quench-flow technique and (2) the kinetics of interaction of Dns-C,-Cho with the acetylcholine receptor sites using the rapid-mixing stopped-flow techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
1
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 52 publications
6
78
1
1
Order By: Relevance
“…Taking the value of 0.5 #M as an average, this would suggest that half-maximal activation would occur at ~50 #M ACh. This value is in good agreement with actual measurements on BC3H-1 cells (Sine and Taylor, 1980;Brett et al, 1986) and on Torpedo membrane fragments (Neubig and Cohen, 1980;Heidmann et al, 1983), although it should be pointed out that the half-maximal concentration is liable to be voltage sensitive in cases where the response is voltage sensitive (as observed here for nearly all combinations).…”
Section: Each Is Roughly As Expectedsupporting
confidence: 92%
“…Taking the value of 0.5 #M as an average, this would suggest that half-maximal activation would occur at ~50 #M ACh. This value is in good agreement with actual measurements on BC3H-1 cells (Sine and Taylor, 1980;Brett et al, 1986) and on Torpedo membrane fragments (Neubig and Cohen, 1980;Heidmann et al, 1983), although it should be pointed out that the half-maximal concentration is liable to be voltage sensitive in cases where the response is voltage sensitive (as observed here for nearly all combinations).…”
Section: Each Is Roughly As Expectedsupporting
confidence: 92%
“…Moreover, accurate measurements made by Thierry Heidmann demonstrated that chlorpromazine binds to just one high-affinity site per 2α.β.γ.δ oligomer (95). The kinetics of access to this site increased 100-fold when chlorpromazine was rapidly mixed with acetylcholine under conditions expected to open the ion channel (96)(97)(98). We thus proposed that chlorpromazine binds to a site located within the ion channel, along the pseudosymmetry axis, that becomes accessible to chlorpromazine when the ion channel opens.…”
Section: Identification Of the Ion Channelmentioning
confidence: 99%
“…In fact, some 20 years earlier Katz and Thesleff (1957) proposed a cyclic mechanism involving a desensitized state with increased agonist affinity relative to the resting state, and such a mechanism accounted for the observed time and concentration dependencies of the agonist-induced affinity increase (Weiland et al, 1977). Coincidence between the agonist-induced affinity increase and functional desensitization was demonstrated using dual measurements of agonist binding and activation (Sine and Taylor, 1979;Neubig et al, 1982;Heidmann et al, 1983). The emerging picture of the ligand binding site indicated a dynamic structure designed to shuttle among functional states to elicit the biological response following brief exposure to ACh and an attenuated response following prolonged exposure.…”
Section: Early Advances (1950s Through 1970s)mentioning
confidence: 99%